Short communication: Secondary dormancy in diplotaxis erucoides: a poáible adaptative strategy as an annual weed - Martinez Laborde, J.B.=700 1 Pita Villamil, J.M.; Perez Garcia, F.
(En, Es)
Ilus., 24 ref.
Keywords: DIPLOTAXIS BRAáICACEAE; GERMINACION; DORMICION<<SEMILLAS; ACIDO GIBERELICO; ALMACENAMIENTO; BANCO DE GENES; ESPAÑA